2004
DOI: 10.1208/aapsj060430
|View full text |Cite
|
Sign up to set email alerts
|

The role of halogen substitution in classical cannabinoids: A CB1 pharmacophore model

Abstract: The presence of halogens within the classical cannabinoid structure leads to large variations in the compounds' potencies and affinities for the CB1 receptors. To explore the structure activity relationships within this class of analogs we have used a series of halogen-substituted (-)-∆ 8 -tetrahydrocannabinol analogs and compared their affinities for the CB1 cannabinoid receptor. Our results indicate that halogen substitution at the end-carbon of the side chain leads to an enhancement in affinity with the bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 33 publications
(47 reference statements)
2
48
0
Order By: Relevance
“…Optimal activity is obtained with a seven or eight carbon length substituted with 1′,1′-or 1′,2′-dimethyl groups as was first demonstrated by Adams (e.g. 2) [52][53][54], while incorporation of halogen, cyano or azido group at the end of the side chain enhances CB1 affinity [55][56][57][58][59][60]. Thus, AM087 (3a) and O-581 (3b) bearing bromo and cyano substituents respectively at the end of the dimethylpentyl side chain exhibit subnanomolar affinities for the CB1 receptor.…”
Section: Classical Cannabinoidsmentioning
confidence: 97%
“…Optimal activity is obtained with a seven or eight carbon length substituted with 1′,1′-or 1′,2′-dimethyl groups as was first demonstrated by Adams (e.g. 2) [52][53][54], while incorporation of halogen, cyano or azido group at the end of the side chain enhances CB1 affinity [55][56][57][58][59][60]. Thus, AM087 (3a) and O-581 (3b) bearing bromo and cyano substituents respectively at the end of the dimethylpentyl side chain exhibit subnanomolar affinities for the CB1 receptor.…”
Section: Classical Cannabinoidsmentioning
confidence: 97%
“…Structure–activity relationship (SAR) studies with classical cannabinoids have shown that the C3 alkyl chain lengths and ω -substitutions modulate ligand affinity. Also, incorporation of a C1′ -gem-dimethyl group affects the conformational properties of the alkyl chain and leads to notable enhancement in potency and efficacy 811 . Unlike Δ 9 -THC, which has a shorter alkyl chain ( n -pentyl), our results show that longer alkyl chains coupled with a C1′ -gem-dimethyl group allow extended interactions with CB 1 , while the C1′ -gem-dimethyl group forms hydrophobic interactions with Phe200 3.36 , Leu359 6.51 and Met363 6.55 (Fig.…”
mentioning
confidence: 99%
“…41 To explore the structure activity relationships and the effect of halogen substitution we synthesized some derivatives possessing a chlorine atom or a trifluoromethyl group in the para position of the styryl group and compared their affinities for the cannabinoid receptors (CB 1 and CB 2 ). H NMR spectra of 3a-d and 4a-f show a singlet at δ H 10.39-10.83 ppm due to the OH-2' proton resonance, which is absent in the spectra of compounds 5a-d and 6a-f.…”
Section: Chemistrymentioning
confidence: 99%